BURNOUT IN THE WORKPLACE - Karin Calitz (Obiter, 2022)
Burnout, defined as chronic workplace stress that has not been successfully managed, has reached epidemic proportions in many countries. The condition has a profound impact on the health and well-being of individuals suffering from it as well as on their families, the workplace, and the economy. Mental and physical exhaustion, cynicism, reduced accomplishment, and mental impairment have been identified as dimensions of burnout. Research indicated that workplace culture and psychosocial risk factors such as overworking, tight deadlines, and long hours contribute to burnout. Current South African legislation does not offer sufficient protection to employees regarding mental illness caused by burnout. Consequently, measures incorporated into European health and safety legislation to prevent burnout and to deal with it once it has occurred, as well as judgments handed down in Australia and the United Kingdom regarding measures that employers should have taken to comply with their duty of care in respect of the mental health of their employees, may provide valuable guidance to South Africa. The article concludes by recommending that burnout be recognised as a distinguishable disease in South Africa; that the Occupational Health and Safety Act 85 of 1993 be amended to require employers to assess psychosocial risks at their workplace and to address these risks; that a code on psychosocial safety in the workplace be adopted guiding employers to recognise the symptoms of burnout and how to support affected employees; that regular working hours be reduced to 40 hours; that a national code as well as an individual code for each workplace be adopted on the right to disconnect; that amendments to the Basic Conditions of Employment Act 75 of 1997 be aligned with an amended Unemployment Insurance Act 63 of 2001 to provide for extended sick leave for burnout; that the Compensation for Occupational Injuries and Diseases Act 130 of 1993 be amended to include burnout as a compensable disease, making provision for psychotherapy, rehabilitation, and reintegration of employees suffering from burnout in the workplace.